International business performance and the enhancers of the internationalization strategy in Portuguese firms - Lobo, Carla Azevedo (2019)
As business has become increasingly global, firms have been defied to develop a distinct approach in terms of business resources, skills and capabilities. The way in which these factors are organized and directed depend upon the role played by the entrepreneur within the company. In other words, the entrepreneur's role can define the company's ability to acquire and operationalize its resources, thus being able to influence business performance, especially of international businesses. Research on factors affecting internationalization is attracting growing interest, but few empirical works focus on the perspective of the entrepreneur. Aiming to analyze the existence of an association between international business performance and the factors that act, on the entrepreneur perspective, as enhancers of the internationalization strategy, an online questionnaire survey was conducted with several variables, based on the literature review. Data collected from the 311 valid responses (Portuguese international firms) were treated by IBM SPSS Statistics 24.0 software. The statistical analyses used were Descriptive Analysis (frequency analysis, descriptive statistics and graphical representations), Inferential Analysis (Spearman´s ordinal correlation, Kruskall-Wallis Test and Chi-Square Test), Reliability Analysis (Cronbach´s alpha) and Categorical Principal Components Analysis (CATPCA). In accordance with International New Ventures Theory, the Strategic Choice view and Network theory, we found evidence of the positive correlation between international experience of the employees and the percentage of business that resulted from internationalization. We also concluded that there is evidence of the importance of specific skills of the employees, of propensity to take risks and the importance of Networks, in international business performance.